2019
DOI: 10.1093/condor/duy001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in mortality rates for Whimbrels (Numenius phaeopus) using the Western Atlantic Flyway

Abstract: For most shorebird species, our understanding of the basic limiting factors and when or where they operate during the annual cycle is currently inadequate to either understand ongoing declines or effectively allocate conservation resources for recovery. Whimbrels (Numenius phaeopus) exhibit delayed recruitment and have low fecundity, and populations with such life-history traits are often vulnerable to increases in adult mortality. We tracked 33 adult Whimbrels with satellite transmitters for 12,802 bird-days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 57 publications
2
33
3
Order By: Relevance
“…Given the difficulty of tracking migrants throughout their annual cycles, few studies have explored their seasonal survival. The majority of studies that have succeeded in developing such estimates have identified migration as the period with the lowest daily (and seasonal) survival rates of the annual cycle (Sillett and Holmes, 2002;Hebblewhite and Merrill, 2011;Klaassen et al, 2014;Romer et al, 2015;Watts et al, 2019). Our results are not entirely consistent with these findings: migratory flights over Europe during both north-and southward migration were consistently characterized by hazard rates that were equivalent to those exhibited during other, stationary, portions of the godwit annual cycle.…”
Section: Seasonal Survival In Migratory Speciescontrasting
confidence: 70%
See 1 more Smart Citation
“…Given the difficulty of tracking migrants throughout their annual cycles, few studies have explored their seasonal survival. The majority of studies that have succeeded in developing such estimates have identified migration as the period with the lowest daily (and seasonal) survival rates of the annual cycle (Sillett and Holmes, 2002;Hebblewhite and Merrill, 2011;Klaassen et al, 2014;Romer et al, 2015;Watts et al, 2019). Our results are not entirely consistent with these findings: migratory flights over Europe during both north-and southward migration were consistently characterized by hazard rates that were equivalent to those exhibited during other, stationary, portions of the godwit annual cycle.…”
Section: Seasonal Survival In Migratory Speciescontrasting
confidence: 70%
“…Similarly, our understanding of the location and timing of mortality events during the annual cycles of migratory species has developed rapidly over the past two decades. While most efforts to determine the seasonal survival rates of migratory species have relied on color-marking schemes and mark-recapture analyses to infer when and where individuals die (Sillett and Holmes, 2002;Lok et al, 2015), some recent studies have used satellite tracking devices to monitor the survival of individuals continuously throughout their annual cycles (Hebblewhite and Merrill, 2011;Klaassen et al, 2014;Hewson et al, 2016;Watts et al, 2019). In general, these studies have identified migration as the period during the annual cycle with the highest mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…All Whimbrels in our study moved exclusively within the Pacific Americas Flyway. In contrast, Whimbrels breeding on the Mackenzie River Delta in Canada, ~ 600 km east of the Colville River, migrate within the Atlantic Americas Flyway (Watts et al 2019), indicating a possible migratory divide between these breeding populations. The nonstop migratory flights of Whimbrels in our study (e.g., ~ 8700 km between Santo Domingo, Chile, and agricultural lands near Calipatria, California) are among the longest recorded for landbirds (Conklin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In North America, efforts to describe the movements of Whimbrels have focused on those using the Atlantic Americas Flyway. Watts et al (2019) found that birds breeding as far west as the Mackenzie River Delta, Canada (i.e., eastern part of western population), migrated to non‐breeding sites located primarily along the northeast coast of South America. Johnson et al (2016) found that individuals breeding near Churchill, Manitoba, either made nonstop flights between breeding and non‐breeding sites along the northeast coast of South America or stopped en route at one of two sites (Chesapeake Bay/Delmarva Peninsula, USA, and coasts of Georgia/South Carolina, USA) on the mid‐Atlantic coast of North America (Johnson et al 2016).…”
mentioning
confidence: 99%
“…The Alaskan population migrates south along the Pacific Flyway to winter areas from Panama through Chile 6 – 8 . Both the Hudson Bay and Mackenzie Delta populations migrate south along the Western Atlantic Flyway to a common winter ground along the northern coast of South America 6 , 9 , 10 . Both of these populations make trans-Atlantic flights to reach winter grounds.…”
mentioning
confidence: 99%